Coconut shell columnar activated carbon as well as preparation method and application thereof
By improving the preparation method of coconut columnar activated carbon, its specific surface area and decomposition rate are increased, and the problem of low decomposition rate in traditional activated carbon when catalyzing the decomposition of methyl chloroformate is solved, achieving a more efficient catalytic effect.
Patent Information
- Application Number
- CN202411841943.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-07
AI Technical Summary
The specific surface area of traditional coconut shell columnar activated carbon leads to a low decomposition rate during catalytic decomposition of methyl chloroformate, which makes it impossible to effectively treat this highly toxic chemical.
Coconut shell powder is mixed and impregnated with alkaline solution and then carbonized, and then prepared coconut shell charcoalization material is prepared, and mixed with binder and metal salt solution for impregnation and calcination activation, so as to prepare coconut shell columnar activated carbon with a high specific surface area.
The specific surface area and decomposition rate of coconut columnar activated carbon can be improved, and the decomposition of methyl chloroformate can be more efficiently catalyzed, reducing the corrosion risk to industrial equipment.
Smart Images

Figure CN119569054A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of activated carbon preparation, and in particular to a coconut shell columnar activated carbon and a preparation method and application thereof. Background Art
[0002] Activated carbon refers to a general term for a carbon material with strong specific adsorption capacity that is prepared by pyrolysis and activation of carbon-containing raw materials such as wood, coal and petroleum coke. It has a developed pore structure, a large specific surface area and abundant surface chemical groups. It also has stable chemical properties, such as good acid and alkali resistance and high strength.
[0003] Among them, coconut shell columnar activated carbon is often used in the field of catalysis due to its rich microporous structure and high product purity, such as catalyzing the decomposition of methyl chloroformate. Methyl chloroformate is a common organic synthesis intermediate, which is used in the pesticide industry to prepare herbicides such as chloramphenicol and bactericides such as carbendazim. However, methyl chloroformate is a highly toxic chemical and has a strong irritating effect on the respiratory tract and conjunctiva. After contact, people show burns to the eyes and upper respiratory tract, and pulmonary edema occurs when the concentration is high. Its irritation intensity is 5 times that of chlorine. In addition, methyl chloroformate is easy to dissociate into chloride ions, which are easy to corrode metal pipelines and containers, and have high requirements on the materials of industrial equipment. However, the specific surface area of traditional coconut shell columnar activated carbon is small, and the decomposition rate is low when catalyzing the decomposition of methyl chloroformate. Therefore, it is urgent to provide a coconut shell columnar activated carbon with a high specific surface area, which can be used to catalyze the decomposition of methyl chloroformate and improve its decomposition rate. Summary of the invention
[0004] Based on this, some embodiments of the present application provide a coconut shell columnar activated carbon and a preparation method thereof, which can increase its specific surface area and improve its decomposition rate when used to catalyze the decomposition of methyl chloroformate.
[0005] In addition, some other embodiments of the present application also provide an application of coconut shell columnar activated carbon in catalyzing the decomposition of methyl chloroformate.
[0006] A method for preparing coconut shell columnar activated carbon comprises the following steps:
[0007] The coconut shell powder is mixed with an alkaline solution and then carbonized to prepare a coconut shell carbonized material;
[0008] The coconut shell carbonized material is mixed with a binder and a solvent and extruded to form a columnar carbon;
[0009] The pillared carbon is mixed and impregnated with a metal salt solution to prepare a metal salt-loaded pillared carbon, wherein the metal salt solution includes one or more of a potassium salt solution and a sodium salt solution;
[0010] The metal salt-loaded columnar carbon is calcined and activated to prepare coconut shell columnar activated carbon.
[0011] In some embodiments, the metal salt solution includes one or more of a sodium nitrate solution, a potassium nitrate solution, a sodium carbonate solution and a potassium carbonate solution.
[0012] In some embodiments, the metal salt solution includes one or both of a sodium nitrate solution and a potassium nitrate solution.
[0013] In some embodiments, the mass percentage concentration of the metal salt solution is 5% to 15%.
[0014] In some of the embodiments, the mass ratio of the columnar carbon to the metal salt solution is 1:(1-10).
[0015] In some of the embodiments, the mass ratio of the columnar carbon to the metal salt solution is 1:(3-5).
[0016] In some embodiments, the step of mixing and impregnating the coconut shell powder with the alkaline solution and then carbonizing the mixture satisfies one or more of the following conditions:
[0017] (1) The carbonization temperature is 300°C to 480°C, and the time is 1h to 4h;
[0018] (2) The heating rate of the carbonization process is 3°C / min~10°C / min;
[0019] (3) The temperature of the mixed immersion of the coconut shell powder and the alkaline solution is 80° C. to 90° C., and the time is 16 h to 24 h;
[0020] Optionally, the mass volume ratio of the coconut shell powder to the alkaline solution is (15g~25g): (100mL~300mL), wherein the concentration of the alkaline solution is 0.1mol / L~1.0mol / L;
[0021] Optionally, the alkaline solution includes one or both of a sodium hydroxide solution and a potassium hydroxide solution;
[0022] (4) The mesh size of the coconut shell powder is 100-250 meshes. Optionally, the mesh size of the coconut shell powder is 150-200 meshes.
[0023] In some embodiments, the step of mixing and extruding the coconut shell carbonized material with a binder and a solvent satisfies one or more of the following conditions:
[0024] (1) The binder includes one or more of casein glue, coal tar, liquid asphalt, epoxy resin, urea-formaldehyde resin and modified starch. Optionally, the binder includes casein glue;
[0025] (2) The mass ratio of the coconut shell carbonized material, the binder and the solvent is 100: (20-50): (5-30);
[0026] (3) The solvent includes one or both of water and glycerol;
[0027] (4) The extrusion molding temperature is 10°C to 45°C.
[0028] In some embodiments, the steps of calcining and activating the metal salt-loaded pillared carbon meet one or more of the following conditions:
[0029] (1) The calcination temperature is 900℃~1100℃ and the calcination time is 8h~12h;
[0030] (2) The heating rate during the calcination process is 3℃ / min~10℃ / min;
[0031] (3) Water vapor is introduced for activation at a flow rate of 0.5 mL / min to 1.5 mL / min.
[0032] In some of the embodiments, the method further comprises: washing the coconut shell columnar activated carbon with acid.
[0033] In some of the embodiments, in the pickling step, a hydrochloric acid solution with a mass percentage concentration of 3% to 5% is used, and the mass ratio of the hydrochloric acid solution to the coconut shell columnar activated carbon is (4 to 6):1.
[0034] In some embodiments, the pickling time is 8h~12h.
[0035] A coconut shell columnar activated carbon, wherein the specific surface area of the coconut shell columnar activated carbon is not less than 1100m 2 / g, the coconut shell columnar activated carbon is loaded with one or more of sodium oxide and potassium oxide.
[0036] In some of the embodiments, the strength of the coconut shell columnar activated carbon is greater than 97%.
[0037] In some embodiments, the pore volume of the coconut shell columnar activated carbon is 0.1 cm 3 / g~1cm 3 / g, and the average pore size is 1nm~10nm.
[0038] In some of the embodiments, the coconut shell columnar activated carbon is prepared by the above-mentioned preparation method.
[0039] For example, the coconut shell columnar activated carbon is used in catalyzing the decomposition reaction of methyl chloroformate.
[0040] In some embodiments, the reaction temperature is 110°C to 130°C, the reaction pressure is 0.5MPa to 0.8MPa, and the gas space velocity is 6000h -1 ~30000h -1 .
[0041] In some of the embodiments, a protective gas is also introduced during the reaction, and the flow rate of the protective gas is 500 mL / min~1200 mL / min.
[0042] In some of the embodiments, the methyl chloroformate is introduced in the form of a mixed liquid of methyl chloroformate and dimethyl carbonate, the mass flow rate of the mixed liquid is 0.8 g / min~4.0 g / min, and the concentration of methyl chloroformate in the mixed liquid is 250 ppm~10000 ppm by mass.
[0043] The preparation method of the coconut shell columnar activated carbon is to carbonize the coconut shell powder mixed with the alkaline solution and impregnated, so that the organic matter in the coconut shell powder is converted into carbon, and the volatile components escape to form a carbonized material with a porous structure. At the same time, the alkaline solution reacts with the oxygen-containing functional groups formed on the surface of the coconut shell powder, and a large number of micropores and mesopores are created during the carbonization process, thereby increasing the specific surface area of the activated carbon. The columnar carbon is obtained by mixing the coconut shell carbonized material with a binder and a solvent and extruding it. The columnar carbon is impregnated with a metal salt solution, so that the columnar carbon is loaded with sodium salt and / or potassium salt. On the one hand, the formation of micropores and pores in the activated carbon is increased, and its specific surface area is increased. On the other hand, compared with other metal salts, it is beneficial to increase the decomposition rate of the prepared coconut shell columnar activated carbon to methyl chloroformate. By roasting and activation treatment, the coconut shell columnar activated carbon is obtained, and its active sites are increased, and its specific surface area is further increased. Therefore, the preparation method of the coconut shell columnar activated carbon is beneficial to increasing its specific surface area, and when used for decomposing methyl chloroformate, it can improve its decomposition rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0045] Figure 1 A schematic diagram of a process flow of a method for preparing coconut shell columnar activated carbon according to some embodiments of the present application;
[0046] Figure 2 A schematic diagram of a process flow of a method for preparing coconut shell columnar activated carbon according to other embodiments of the present application. DETAILED DESCRIPTION
[0047] In order to facilitate the understanding of the present application, the present application will be described more comprehensively below in conjunction with the specific embodiments. The preferred embodiments of the present application are provided in the specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0049] Unless otherwise specified or there is a contradiction, the terms and phrases used in this application have the following meanings:
[0050] In this application, "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features.
[0051] In the description of the present application, “plurality” means at least two, for example, two, three, etc., unless otherwise clearly and specifically defined.
[0052] In this application, "one or several" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0053] In this application, the percentage concentration involved, unless otherwise specified, refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.
[0054] In this document, "further", "further", "particularly", "for example", "such as", "example", "for example", etc. are used for descriptive purposes, indicating that the previous and subsequent technical solutions are related in terms of the content covered, but should not be understood as a limitation on the previous technical solution, nor can it be understood as a limitation on the protection scope of this document. In this document, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0055] Herein, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If multiple "optional" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" item is independent of each other. In this application, descriptions such as "optionally contain", "optionally include", etc. mean "contain or not contain". "Optional component X" means that component X exists or does not exist, or means that component X is contained or not contained.
[0056] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.
[0057] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0058] The terms "including" and "having" and any variations thereof in the embodiments of the present application are intended to cover non-exclusive inclusions. For example, a process, method, system, product, or device that includes a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units that are not listed, or may optionally include other steps or components that are inherent to these processes, methods, products, or devices.
[0059] Reference to "embodiments" in this application means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application may be combined with other embodiments.
[0060] The first aspect of the present application provides a method for preparing coconut shell columnar activated carbon. Figure 1 , including the following steps S110, S120, S130 and S140:
[0061] Step S110: mixing coconut shell powder with an alkaline solution, impregnating the mixture, and then carbonizing the mixture to prepare a carbonized coconut shell material.
[0062] Step S120: mixing the coconut shell carbonized material with a binder and a solvent, and extruding the mixture to form a columnar carbon.
[0063] Step S130: Mixing and impregnating the pillared carbon with a metal salt solution to prepare the metal salt-loaded pillared carbon, wherein the metal salt solution includes one or more of a potassium salt solution and a sodium salt solution.
[0064] Step S140: calcining and activating the metal salt-loaded columnar carbon to prepare coconut shell columnar activated carbon.
[0065] The preparation method of the coconut shell columnar activated carbon is to carbonize the coconut shell powder mixed with the alkaline solution and impregnated, so that the organic matter in the coconut shell powder is converted into carbon, and the volatile components escape to form a carbonized material with a porous structure. At the same time, the alkaline solution reacts with the oxygen-containing functional groups formed on the surface of the coconut shell powder, and a large number of micropores and mesopores are created during the carbonization process, thereby increasing the specific surface area of the activated carbon. The columnar carbon is obtained by mixing the coconut shell carbonized material with a binder and a solvent and extruding it. The columnar carbon is impregnated with a metal salt solution, so that the columnar carbon is loaded with sodium salt and / or potassium salt. On the one hand, the formation of micropores and pores in the activated carbon is increased, and its specific surface area is increased. On the other hand, compared with other metal salts, it is beneficial to increase the decomposition rate of the prepared coconut shell columnar activated carbon to methyl chloroformate. By roasting and activation treatment, the coconut shell columnar activated carbon is obtained, and its active sites are increased, and its specific surface area is further increased. Therefore, the preparation method of the coconut shell columnar activated carbon is beneficial to increasing its specific surface area, and when used for decomposing methyl chloroformate, it can improve its decomposition rate.
[0066] The following is a detailed description of each step:
[0067] Step S110: mixing coconut shell powder with an alkaline solution, impregnating the mixture, and then carbonizing the mixture to prepare a carbonized coconut shell material.
[0068] In some embodiments, the mesh size of the coconut shell powder is 100 mesh to 250 mesh. Optionally, the mesh size of the coconut shell powder is 150 mesh to 200 mesh.
[0069] Specifically, the coconut shell powder is obtained by the following steps: grinding and sieving the coconut shell, washing with deionized water, and drying after washing to obtain the coconut shell powder. In one example, the washing times with deionized water are 3 to 5 times. In one example, the drying temperature is 110°C to 120°C.
[0070] In some embodiments, the temperature of the mixed impregnation of coconut shell powder and alkaline solution is 80°C to 90°C, and the time is 16h to 24h. For example, the temperature of the mixed impregnation can be but not limited to 80°C, 82°C, 84°C, 85°C, 86°C, 88°C, 90°C or a range consisting of any two of these values. The time of mixed impregnation can be but not limited to 16h, 18h, 20h, 22h, 24h or a range consisting of any two of these values. By adding alkaline solution for impregnation and activation, it reacts with the oxygen-containing functional groups formed on the surface of the coconut shell powder, and during the carbonization process, a large number of micropores and mesopores are created, further increasing the specific surface area of the activated carbon.
[0071] Specifically, the mass volume ratio of coconut shell powder to alkaline solution is (15g~25g): (100mL~300mL), wherein the concentration of the alkaline solution is 0.1mol / L~1.0mol / L. For example, the concentration of the alkaline solution can be, but is not limited to, 0.1mol / L, 0.2mol / L, 0.4mol / L, 0.6mol / L, 0.8mol / L, 1.0mol / L or a range consisting of any two of these values. The strength of the activated carbon is effectively improved by controlling the concentration and addition amount of the alkaline solution.
[0072] Specifically, the alkaline solution includes one or both of a sodium hydroxide solution and a potassium hydroxide solution.
[0073] In some embodiments, the carbonization temperature is 300°C to 480°C, and the time is 1h to 4h. For example, the carbonization temperature may be, but is not limited to, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 450°C, 480°C, or a range consisting of any two of these values. The carbonization time may be, but is not limited to, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, or a range consisting of any two of these values.
[0074] In some embodiments, the heating rate of the carbonization process is 3°C / min to 10°C / min. For example, the heating rate of the carbonization process may be, but is not limited to, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or a range consisting of any two of these values.
[0075] In some embodiments, after the carbonization step, the step further includes: washing with deionized water until neutral, and drying. In one example, the drying temperature is 110°C to 120°C.
[0076] In some embodiments, step S110 includes: mixing coconut shell powder and alkaline solution at 80°C to 90°C and soaking for 16h to 24h, wherein the mesh size of coconut shell powder is 100 mesh to 250 mesh, the mass volume ratio of coconut shell powder to alkaline solution is (15g to 25g): (100mL to 300mL), and the concentration of alkaline solution is 0.1mol / L to 1mol / L. Then, the temperature is raised to 300°C to 480°C at a heating rate of 3°C / min to 10°C / min for carbonization for 1h to 4h.
[0077] Step S120: mixing the coconut shell carbonized material with a binder and a solvent, and extruding the mixture to form a columnar carbon.
[0078] In some embodiments, the binder includes one or more of casein glue, coal tar, liquid asphalt, epoxy resin, urea-formaldehyde resin and modified starch. Optionally, the binder includes casein glue. The activated carbon prepared using the casein glue binder has significantly higher strength, and trace amounts of sodium ions and / or potassium ions are uniformly incorporated into the activated carbon through the binder, thereby improving the conversion rate of activated carbon to methyl chloroformate.
[0079] In some embodiments, the mass ratio of coconut shell carbonized material, binder and solvent is 100: (20-50): (5-30). For example, the mass ratio of coconut shell carbonized material to binder can be, but not limited to, 100:20, 100:25, 100:30, 100:35, 100:40, 100:45, 100:50 or a range consisting of any two of these values. The mass ratio of coconut shell carbonized material to solvent can be, but not limited to, 100:5, 100:8, 100:10, 100:12, 100:15, 100:18, 100:20, 100:22, 100:25, 100:28, 100:30 or a range consisting of any two of these values.
[0080] In some embodiments, the solvent includes one or both of water and glycerol.
[0081] In some embodiments, the extrusion molding temperature is 10° C. to 45° C. For example, the extrusion molding temperature can be, but is not limited to, 10° C., 15° C., 20° C., 25° C., 30° C., 35° C., 40° C., 45° C., or a range consisting of any two of these values.
[0082] In some embodiments, the extrusion step is performed in a kneader.
[0083] In some embodiments, after the extrusion molding step, the step further includes drying at room temperature for 24 hours to 48 hours. The room temperature may be, for example, but not limited to, 10° C. to 30° C.
[0084] In some embodiments, step S120 includes: mixing coconut shell carbonized material with a binder and a solvent in a mass ratio of 100: (20-50): (5-30), extruding and molding at 10°C-45°C, and drying at room temperature for 24h-48h to prepare columnar carbon.
[0085] Step S130: Mixing and impregnating the pillared carbon with a metal salt solution to prepare the metal salt-loaded pillared carbon, wherein the metal salt solution includes one or more of a potassium salt solution and a sodium salt solution.
[0086] In some embodiments, the metal salt solution includes one or more of a sodium nitrate solution, a potassium nitrate solution, a sodium carbonate solution, and a potassium carbonate solution. Alternatively, the metal salt solution includes one or both of a sodium nitrate solution and a potassium nitrate solution.
[0087] In some embodiments, the mass percentage concentration of the metal salt solution is 5% to 15%. For example, the concentration of the metal salt solution can be, but is not limited to, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 15%, or a range consisting of any two of these values. In one example, the mass percentage concentration of the metal salt solution is 10%.
[0088] In some embodiments, the mass ratio of the pillared carbon to the metal salt solution is 1:(1-10). For example, the mass ratio of the pillared carbon to the metal salt solution can be, but is not limited to, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:8, 1:10, or a range consisting of any two of these values. Optionally, the mass ratio of the pillared carbon to the metal salt solution is 1:(3-5).
[0089] In some embodiments, after the step of mixing and impregnating the columnar carbon with the metal salt solution, the steps of filtering and drying are also included. In one example, in the drying step, the temperature is 110° C. to 120° C. and the time is 12 h to 18 h.
[0090] In some embodiments, step S130 includes: impregnating the columnar carbon with a metal salt solution, filtering after impregnation, and drying the obtained solid at 110° C. to 120° C. for 12 h to 18 h. The metal salt solution includes one or more of potassium salt and sodium salt, the mass percentage concentration of the metal salt solution is 5% to 15%, and the mass ratio of the columnar carbon to the metal salt solution is 1: (1 to 10).
[0091] Step S140: calcining and activating the metal salt-loaded columnar carbon to prepare coconut shell columnar activated carbon.
[0092] In some embodiments, the calcination temperature is 900°C to 1100°C, and the calcination time is 8h to 12h. For example, the calcination temperature may be, but is not limited to, 900°C, 950°C, 1000°C, 1050°C, 1100°C, or a range consisting of any two of these values. The calcination time may be, but is not limited to, 8h, 9h, 10h, 11h, 12h, or a range consisting of any two of these values.
[0093] In some embodiments, the heating rate of the calcining process is 3°C / min to 10°C / min. For example, the heating rate may be, but is not limited to, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or a range consisting of any two of these values.
[0094] In some embodiments, water vapor is introduced for activation, and the flow rate of water vapor is 0.5 mL / min to 1.5 mL / min. For example, the flow rate of water vapor can be, but is not limited to, 0.5 mL / min, 0.6 mL / min, 0.8 mL / min, 1 mL / min, 1.2 mL / min, 1.4 mL / min, 1.5 mL / min or a range consisting of any two of these values. Water vapor is introduced for activation treatment, so that the carbon element of the columnar carbon reacts with water vapor to create new pores, open pores, and expand pores in situ on the carbon, thereby forming a developed pore structure and increasing its active sites and specific surface area. It is understood that in other embodiments, carbon dioxide can also be used for activation treatment.
[0095] In some embodiments, step S140 includes: heating the metal salt-loaded columnar carbon to 900°C~1100°C under a protective atmosphere at a rate of 3°C / min~10°C / min for 8h~12h, and simultaneously introducing water vapor at a flow rate of 0.5mL / min~1.5mL / min for activation.
[0096] In some embodiments, the method for preparing coconut shell columnar activated carbon further comprises: a step of acid washing the coconut shell columnar activated carbon.
[0097] Specifically, in the pickling step, a hydrochloric acid solution with a mass percentage concentration of 3% to 5% is used, and the mass ratio of the hydrochloric acid solution to the coconut shell columnar activated carbon is (4 to 6): 1. For example, the mass ratio of the hydrochloric acid solution to the coconut shell columnar activated carbon can be, but is not limited to, 4: 1, 4.5: 1, 5: 1, 5.5: 1, 6: 1 or a range consisting of any two of these values. It can be understood that in other embodiments, in the pickling step, the acid solution used is not limited to hydrochloric acid, but can also be other commonly used acids, such as sulfuric acid, nitric acid, etc. Considering the difficulty of subsequent wastewater treatment, in some embodiments of the present application, a hydrochloric acid solution is preferably used.
[0098] Specifically, the pickling time is 8 hours to 12 hours. For example, the pickling time can be, but is not limited to, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, or a range consisting of any two of these values.
[0099] Specifically, during acid washing, steam is also introduced for cooking. The high-temperature acid washing of activated carbon further removes unstable metal oxides in the coconut shell of the activated carbon raw material and on the surface, while stable metal oxides such as sodium oxide and / or potassium oxide are retained in the pores of the activated carbon, thereby improving the purity of the activated carbon and increasing the number of active site vacancies.
[0100] Specifically, after the pickling step, the steps of washing and drying are also included. In one example, the drying temperature is 110°C to 120°C.
[0101] In some embodiments, see Figure 2 The preparation method of coconut shell columnar activated carbon comprises the following steps:
[0102] Step S210: Mix the coconut shell powder and the alkaline solution at 80°C to 90°C and immerse for 16h to 24h, then heat the mixture to 300°C to 480°C at a heating rate of 3°C / min to 10°C / min for carbonization for 1h to 4h. The mesh size of the coconut shell powder is 100 to 250 meshes, the mass volume ratio of the coconut shell powder to the alkaline solution is (15g to 25g): (100mL to 300mL), and the concentration of the alkaline solution is 0.1mol / L to 1.0mol / L.
[0103] Step S220: Mix the coconut shell carbonized material with a binder and a solvent in a mass ratio of 100: (20-50): (5-30), extrude and mold at 10° C.-45° C., and then dry at room temperature for 24 h-48 h to prepare columnar carbon.
[0104] Step S230: impregnate the columnar carbon with the metal salt solution, filter after impregnation, and dry the obtained solid at 110°C to 120°C for 12h to 18h to obtain the columnar carbon loaded with metal salt. The metal salt solution includes one or more of potassium salt and sodium salt, the mass percentage concentration of the metal salt solution is 5% to 15%, and the mass ratio of the columnar carbon to the metal salt solution is 1: (1 to 10).
[0105] Step S240: The metal salt-loaded columnar carbon is heated to 900°C~1100°C at a rate of 3°C / min~10°C / min under a protective atmosphere for 8h~12h, and water vapor is introduced at a flow rate of 0.5mL / min~1.5mL / min for activation to obtain coconut shell columnar activated carbon.
[0106] Step S250: Mix the coconut shell columnar activated carbon with a hydrochloric acid solution having a mass percentage concentration of 3% to 5% in a mass ratio of 1: (4 to 6), and at the same time, introduce steam for 8h to 12h to obtain purified coconut shell columnar activated carbon.
[0107] The method for preparing coconut shell columnar activated carbon in the above embodiment has at least the following advantages:
[0108] (1) In the preparation method of coconut shell columnar activated carbon in some of the above embodiments, an alkaline solution is added for impregnation and activation, and reacts with the oxygen-containing functional groups formed on the surface of coconut shell powder. During the carbonization process, a large number of micropores and mesopores are created, further increasing the specific surface area of the activated carbon. In addition, the strength of the activated carbon is effectively improved by controlling the concentration and amount of the alkaline solution.
[0109] (2) The preparation methods of coconut shell columnar activated carbon in some of the above embodiments precisely control the pore structure of the activated carbon by controlling the heating rate, carbonization temperature, activation temperature and water vapor addition rate.
[0110] (3) The preparation method of coconut shell columnar activated carbon in some of the above embodiments further improves the strength of the activated carbon by optimizing the type of binder, and evenly incorporates trace amounts of sodium ions and / or potassium ions into the activated carbon through the binder, thereby improving the conversion rate of the activated carbon to methyl chloroformate.
[0111] (4) The preparation method of coconut shell columnar activated carbon in some of the above embodiments further removes unstable metal oxides in the activated carbon by high-temperature acid washing of the activated carbon, thereby improving the purity of the activated carbon and increasing the number of active site vacancies.
[0112] (5) The preparation method of coconut shell columnar activated carbon in some of the above embodiments provides an activated carbon with high specific surface area, high strength and low impurities, with a sulfur content of less than 1000 ppm, a phosphorus content of less than 1000 ppm, and a chlorine content of less than 500 ppm; a specific surface area of more than 1100 m 2 / g, pore volume 0.1cm 3 / g~1cm 3 / g, pore size is 1nm~10nm; strength is greater than 97%. The rich mesoporous structure, active sites and low impurity content of coconut shell columnar activated carbon are helpful to improve the decomposition efficiency of methyl chloroformate.
[0113] It should be understood that Figure 1 and Figure 2 The schematic diagram of the process for preparing coconut shell columnar activated carbon in two embodiments of the present application is shown in FIG. Figure 1 and Figure 2The steps in the flowchart are shown in sequence as indicated by the arrows, but these steps are not necessarily performed in the order indicated by the arrows. Unless otherwise specified in this document, there is no strict order restriction for the execution of these steps, and they can be performed in other orders. Figure 1 and Figure 2 At least part of the steps may include multiple sub-steps or multiple stages. These sub-steps or stages are not necessarily executed at the same time, but can be executed at different times. The order of execution is not necessarily sequential, but can be executed in turn or alternately with other steps or at least part of other sub-steps or stages.
[0114] The second aspect of the present application provides a coconut shell columnar activated carbon having a specific surface area of not less than 1100 m 2 / g, coconut shell columnar activated carbon is loaded with one or more of sodium oxide and potassium oxide.
[0115] For example, the specific surface area of coconut shell columnar activated carbon can be, but is not limited to, 1100 m 2 / g, 1150m 2 / g、1200m 2 / g, 1250m 2 / g、1300m 2 / g, 1350m 2 / g、1400m 2 / g or a range consisting of any two of these values. In some embodiments, the specific surface area of the coconut shell columnar activated carbon is not less than 1200m 2 / g. Optionally, the specific surface area of the coconut shell columnar activated carbon is not less than 1300m 2 / g.
[0116] In some embodiments, the strength of the coconut shell columnar activated carbon is greater than 97%. Exemplarily, the strength of the coconut shell columnar activated carbon can be, but is not limited to, 97%, 97.2%, 97.5%, 97.8%, 98%, 98.2%, 98.5%, 98.8%, 99%, 99.2%, 99.5%, 99.8% or a range consisting of any two of these values. Optionally, the strength of the coconut shell columnar activated carbon is greater than 97.5%. Optionally, the strength of the coconut shell columnar activated carbon is greater than 98%.
[0117] In this application, the strength of coconut shell columnar activated carbon refers to its wear resistance, that is, the performance of resistance to wear or friction. It is generally expressed as a percentage. The larger the percentage, the higher the strength, the stronger the stability, and the higher the efficiency of use. The determination method is: the activated carbon is placed in a special plate with a certain number of stainless steel balls, and a combination of timed rotation and beating is performed. During the movement, the skeleton and surface of the activated carbon are destroyed at the same time. The change in particle size of the destroyed activated carbon is measured, and the percentage of the sample retained on the strength test sieve is used as the strength of the activated carbon.
[0118] In some embodiments, the pore volume of the coconut shell columnar activated carbon is 0.1 cm 3 / g~1cm 3 / g, and the average pore size is 1nm~10nm. For example, the pore volume of coconut shell columnar activated carbon can be but is not limited to 0.1cm 3 / g, 0.2cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.8cm 3 / g, 1cm 3 / g or a range consisting of any two of these values. Optionally, the pore volume of the coconut shell columnar activated carbon is 0.2cm 3 / g~1cm 3 / g. The average pore size of the coconut shell columnar activated carbon can be, but is not limited to, 1nm, 2nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm or a range consisting of any two of these values. Optionally, the average pore size of the coconut shell columnar activated carbon is 1nm to 8nm, or the average pore size of the coconut shell columnar activated carbon is 1nm to 6nm.
[0119] In some embodiments, the coconut shell columnar activated carbon has a sulfur content of less than 1000 ppm, a phosphorus content of less than 1000 ppm, and a chlorine content of less than 500 ppm.
[0120] In some embodiments, coconut shell columnar activated carbon is prepared using the above-mentioned preparation method.
[0121] The coconut shell columnar activated carbon has the advantages of large specific surface area, high strength, few impurities, etc. It also has rich mesoporous and microporous structures and active sites, and is used for the catalytic decomposition of methyl chloroformate with high decomposition efficiency.
[0122] The third aspect of the present application provides an application of coconut shell columnar activated carbon in catalyzing the decomposition reaction of methyl chloroformate.
[0123] In some embodiments, the temperature of the catalytic decomposition reaction of methyl chloroformate is 110° C. to 130° C., the reaction pressure is 0.5 MPa to 0.8 MPa, and the gas space velocity is 6000 h -1 ~30000h -1 . For example, the temperature may be, but is not limited to, 110°C, 112°C, 115°C, 118°C, 120°C, 122°C, 125°C, 128°C, 130°C, or a range consisting of any two of these values. The reaction pressure may be, but is not limited to, 0.5MPa, 0.55MPa, 0.6MPa, 0.65MPa, 0.7MPa, 0.75MPa, 0.8MPa, or a range consisting of any two of these values. The gas space velocity may be, but is not limited to, 6000h -1 、8000h -1 、10000h -1 、12000h -1 、15000h -1 、20000h -1 、25000h -1 、30000h -1 Or a range consisting of any two of these values.
[0124] In some embodiments, a protective gas is also introduced into the catalytic decomposition reaction of methyl chloroformate, and the flow rate of the protective gas is 500 mL / min to 1200 mL / min. For example, the flow rate of the protective gas can be, but is not limited to, 500 mL / min, 600 mL / min, 700 mL / min, 800 mL / min, 900 mL / min, 1000 mL / min, 1100 mL / min, 1200 mL / min, or a range consisting of any two of these values.
[0125] In certain embodiments, methyl chloroformate is passed in the form of a mixed liquid of methyl chloroformate and dimethyl carbonate. In one example, the mass flow rate of the mixed liquid of methyl chloroformate and dimethyl carbonate is 0.8g / min~4.0g / min, and in the mixed liquid of methyl chloroformate and dimethyl carbonate, the methyl chloroformate concentration is 250ppm~10000ppm by mass. For example, the mass flow rate of the mixed liquid of methyl chloroformate and dimethyl carbonate can be but is not limited to 0.8g / min, 1g / min, 1.5g / min, 2g / min, 2.5g / min, 3g / min, 3.5g / min, 4.0g / min or the range formed by any two of these values. In the mixed liquid of methyl chloroformate and dimethyl carbonate, the concentration of methyl chloroformate by mass can be but is not limited to 250 ppm, 500 ppm, 1000 ppm, 2000 ppm, 5000 ppm, 8000 ppm, 10000 ppm or a range consisting of any two of these values.
[0126] In some embodiments, coconut shell columnar activated carbon is placed in a tubular reactor, a mixed liquid of methyl chloroformate and dimethyl carbonate is introduced, and nitrogen is introduced at a flow rate of 500 mL / min~1200 mL / min, the reaction temperature is set to 110°C~130°C, the reaction pressure is 0.5 MPa~0.8 MPa, and the gas space velocity is 6000 h -1 ~30000h -1 , and the reaction is carried out. In which methyl chloroformate and dimethyl carbonate are heated and gasified during the feeding process.
[0127] In one example, the reactor outlet is connected to a jacketed product condensation tank, and the condensation temperature can be, for example but not limited to, 5°C.
[0128] In order to make the purpose and advantages of the present application clearer, the coconut shell columnar activated carbon of the present application and its effects are further described in detail in conjunction with specific examples. It should be understood that the specific examples described herein are only used to explain the present application and shall not be used to limit the present application. The following examples do not include other components except inevitable impurities unless otherwise specified. The drugs and instruments used in the examples are conventionally selected in the art unless otherwise specified. The experimental methods for which specific conditions are not specified in the examples are implemented according to conventional conditions, such as the conditions described in the literature and books or the methods recommended by the manufacturer.
[0129] Example 1-1
[0130] This embodiment provides a coconut shell columnar activated carbon, and the preparation steps are as follows:
[0131] (1) Pretreatment: Grind the coconut shell, pass it through a 170-mesh sieve, wash it three times with deionized water, and dry it in an oven at 120°C to obtain coconut shell powder.
[0132] (2) Carbonization: Weigh 200 g of the coconut shell powder obtained in step (1), add 2000 mL of 1.0 mol / L sodium hydroxide solution, and soak at 80°C for 16 h. After the soaking, control the heating rate to 5°C / min, heat to 300°C for carbonization for 2 h, then cool to room temperature, wash with deionized water until neutral, and finally dry in an oven at 120°C to obtain a coconut shell carbonized material.
[0133] (3) Molding: The coconut shell carbonized material, casein glue and water are loaded into a kneader in a mass ratio of 100:30:10, kneaded evenly, extruded at 45°C, and dried at room temperature for 24 hours to obtain columnar charcoal.
[0134] (4) Impregnation: Sodium nitrate solid is dissolved in deionized water to prepare a sodium nitrate solution with a mass percentage concentration of 10%. The columnar carbon prepared in step (3) is mixed with the sodium nitrate solution in a mass ratio of 1:3, placed in a round-bottom flask, connected to a rotary evaporator, and rotary evaporated at room temperature and atmospheric pressure for one hour. After the impregnation is completed, the solid is filtered and dried in an oven at 120°C for 12 hours.
[0135] (5) Activation: The columnar carbon loaded with metal salt obtained in step (4) was heated to 900°C for 8 h under nitrogen protection at a heating rate of 5°C / min, and water vapor was introduced at a flow rate of 0.5 mL / min for activation. After the calcination was completed, it was cooled to room temperature to obtain coconut shell columnar activated carbon.
[0136] (6) Acid washing: The coconut shell columnar activated carbon obtained in step (5) was mixed with 3% hydrochloric acid in a mass ratio of 1:4, and steam was introduced into the mixture for 8 h. After the acid washing, the mixture was washed with deionized water until neutral, and then dried in an oven at 120° C. to obtain coconut shell columnar activated carbon A.
[0137] The characterization results show that the specific surface area of the coconut shell columnar activated carbon A obtained in this example is 1338.6 m 2 / g, pore volume 0.85cm 3 / g, the average pore size is 4.9nm; the strength is 99.3%, the phosphorus content is 178.4ppm, the sulfur content is 204.5ppm, and the chlorine content is 138.4ppm.
[0138] Example 1-2
[0139] This embodiment provides a coconut shell columnar activated carbon, and the preparation steps are as follows:
[0140] (1) Pretreatment: Grind the coconut shell, pass it through a 170-mesh sieve, wash it three times with deionized water, and dry it in an oven at 120°C to obtain coconut shell powder.
[0141] (2) Carbonization: Weigh 200 g of the coconut shell powder obtained in step (1), add 4000 mL of 1.0 mol / L sodium hydroxide solution, and soak at 90°C for 24 h. After the soaking, control the heating rate to be 10°C / min, heat to 450°C for carbonization for 4 h, then cool to room temperature, wash with deionized water until neutral, and finally dry in an oven at 120°C to obtain the coconut shell carbonized material.
[0142] (3) Molding: The coconut shell carbonized material, casein glue and water are loaded into a kneader in a mass ratio of 100:30:10, kneaded evenly, extruded at 45°C, and dried at room temperature for 24 hours to obtain columnar charcoal.
[0143] (4) Impregnation: Sodium nitrate solid is dissolved in deionized water to prepare a sodium nitrate solution with a mass percentage concentration of 10%. The columnar carbon prepared in step (3) is mixed with the sodium nitrate solution in a mass ratio of 1:5, placed in a round-bottom flask, connected to a rotary evaporator, and rotary evaporated at room temperature and atmospheric pressure for one hour. After the impregnation is completed, the solid is filtered and dried in an oven at 120°C for 12 hours.
[0144] (5) Activation: The columnar carbon loaded with metal salt obtained in step (4) was heated to 1100°C for 12 h under nitrogen protection at a heating rate of 10°C / min, and water vapor was introduced at a flow rate of 1.5 mL / min for activation. After the calcination was completed, it was cooled to room temperature to obtain coconut shell columnar activated carbon.
[0145] (6) Acid washing: The coconut shell columnar activated carbon obtained in step (5) was mixed with a 5% by mass hydrochloric acid solution in a mass ratio of 1:4, and steam was introduced into the mixture for 12 h. After the acid washing, the mixture was washed with deionized water until neutral, and then dried in an oven at 120° C. to obtain coconut shell columnar activated carbon B.
[0146] The characterization results show that the specific surface area of the coconut shell columnar activated carbon B obtained in this example is 1535.5 m 2 / g, pore volume 0.96cm 3 / g, the average pore size is 5.3nm; the strength is 99.1%, the phosphorus content is 104.7ppm, the sulfur content is 179.4ppm, and the chlorine content is 409.3ppm.
[0147] Examples 1-3
[0148] This embodiment provides a coconut shell columnar activated carbon, and the preparation steps are as follows:
[0149] (1) Pretreatment: Grind the coconut shell, pass it through a 170-mesh sieve, wash it three times with deionized water, and dry it in an oven at 120°C to obtain coconut shell powder.
[0150] (2) Carbonization: Weigh 200 g of the coconut shell powder obtained in step (1), add 800 mL of 0.1 mol / L sodium hydroxide solution, and immerse at 90° C. for 20 h. After immersion, control the heating rate to 8° C. / min, heat to 300° C. and carbonize for 1 h. Then cool to room temperature, wash with deionized water until neutral, and finally dry in an oven at 120° C. to obtain a coconut shell carbonized material.
[0151] (3) Molding: The coconut shell carbonized material, casein glue and water are loaded into a kneader in a mass ratio of 100:50:5, kneaded evenly, extruded at 45°C, and dried at room temperature for 24 hours to obtain columnar charcoal.
[0152] (4) Impregnation: Dissolve potassium nitrate solid in deionized water to prepare a potassium nitrate solution with a mass percentage concentration of 10%. Mix the columnar carbon prepared in step (3) with the potassium nitrate solution in a mass ratio of 1:3, place in a round-bottom flask, connect to a rotary evaporator, and perform rotary evaporation at room temperature and atmospheric pressure for one hour. After the impregnation is completed, filter to obtain the solid, and dry in an oven at 120°C for 12 hours.
[0153] (5) Activation: The columnar carbon loaded with metal salt obtained in step (4) was calcined at 1000°C for 8 h under nitrogen protection at a heating rate of 8°C / min, and water vapor was introduced at a flow rate of 0.5 mL / min for activation. After calcination, the columnar carbon was cooled to room temperature to obtain coconut shell columnar activated carbon.
[0154] (6) Acid washing: The coconut shell columnar activated carbon obtained in step (5) was mixed with a 3% hydrochloric acid solution at a mass ratio of 1:5, and steam was introduced into the mixture for 8 h. After the acid washing, the mixture was washed with deionized water until neutral, and then dried in an oven at 120° C. to obtain coconut shell columnar activated carbon C.
[0155] The characterization results show that the specific surface area of the coconut shell columnar activated carbon C obtained in this example is 1384.7 m 2 / g, pore volume 0.32cm 3 / g, the average pore size is 2.1nm; the strength is 99.4%, the phosphorus content is 763.3ppm, the sulfur content is 836.2ppm, and the chlorine content is 248.7ppm.
[0156] Examples 1-4
[0157] This embodiment provides a coconut shell columnar activated carbon, and the preparation steps are as follows:
[0158] (1) Pretreatment: Grind the coconut shell, pass it through a 170-mesh sieve, wash it three times with deionized water, and dry it in an oven at 120°C to obtain coconut shell powder.
[0159] (2) Carbonization: Weigh 200 g of the coconut shell powder obtained in step (1), add 4000 mL of 0.3 mol / L sodium hydroxide solution, and soak at 85°C for 16 h. After the soaking, control the heating rate to 3°C / min, heat to 350°C for carbonization for 2 h, then cool to room temperature, wash with deionized water until neutral, and finally dry in an oven at 120°C to obtain the coconut shell carbonized material.
[0160] (3) Molding: The coconut shell carbonized material, casein glue and water are loaded into a kneader in a mass ratio of 100:30:5, kneaded evenly, extruded at 45°C, and dried at room temperature for 24 hours to obtain columnar charcoal.
[0161] (4) Impregnation: Dissolve potassium nitrate solid in deionized water to prepare a potassium nitrate solution with a mass percentage concentration of 10%. Mix the columnar carbon prepared in step (3) with the potassium nitrate solution in a mass ratio of 1:3, place in a round-bottom flask, connect to a rotary evaporator, and perform rotary evaporation at room temperature and atmospheric pressure for one hour. After the impregnation is completed, filter to obtain the solid, and dry in an oven at 120°C for 12 hours.
[0162] (5) Activation: The columnar carbon loaded with metal salt obtained in step (4) was heated to 900°C for 8 h under nitrogen protection at a heating rate of 3°C / min, and water vapor was introduced at a flow rate of 0.5 mL / min for activation. After the calcination was completed, it was cooled to room temperature to obtain coconut shell columnar activated carbon.
[0163] (6) Acid washing: The coconut shell columnar activated carbon obtained in step (5) was mixed with a 3% hydrochloric acid solution at a mass ratio of 1:6, and steam was introduced into the mixture for 12 h. After the acid washing, the mixture was washed with deionized water until neutral, and then dried in an oven at 120° C. to obtain coconut shell columnar activated carbon D.
[0164] The characterization results show that the specific surface area of the coconut shell columnar activated carbon D obtained in this example is 1364.1 m 2 / g, pore volume 0.39cm 3 / g, the average pore size is 2.9nm; the strength is 99.4%, the phosphorus content is 347.3ppm, the sulfur content is 329.4ppm, and the chlorine content is 467.2ppm.
[0165] Examples 1-5
[0166] This embodiment provides a coconut shell columnar activated carbon, and the preparation steps are as follows:
[0167] (1) Pretreatment: Grind the coconut shell, pass it through a 170-mesh sieve, wash it three times with deionized water, and dry it in an oven at 120°C to obtain coconut shell powder.
[0168] (2) Carbonization: Weigh 200 g of the coconut shell powder obtained in step (1), add 2000 mL of 0.8 mol / L sodium hydroxide solution, and soak at 85°C for 16 h. After the soaking, control the heating rate to 3°C / min, heat to 480°C for carbonization for 4 h, then cool to room temperature, wash with deionized water until neutral, and finally dry in an oven at 120°C to obtain a coconut shell carbonized material.
[0169] (3) Molding: The coconut shell carbonized material, casein glue and water are loaded into a kneader in a mass ratio of 100:30:10, kneaded evenly, extruded at 45°C, and dried at room temperature for 24 hours to obtain columnar charcoal.
[0170] (4) Impregnation: Sodium nitrate solid is dissolved in deionized water to prepare a sodium nitrate solution with a mass percentage concentration of 5%. The columnar carbon prepared in step (3) is mixed with the sodium nitrate solution in a mass ratio of 1:3, placed in a round-bottom flask, connected to a rotary evaporator, and rotary evaporated at room temperature and atmospheric pressure for one hour. After the impregnation is completed, the solid is filtered and dried in an oven at 120°C for 12 hours.
[0171] (5) Activation: The columnar carbon loaded with metal salt obtained in step (4) was heated to 1100°C for 12 h under nitrogen protection at a heating rate of 3°C / min, and water vapor was introduced at a flow rate of 1.5 mL / min for activation. After the calcination was completed, it was cooled to room temperature to obtain coconut shell columnar activated carbon.
[0172] (6) Acid washing: The coconut shell columnar activated carbon obtained in step (5) was mixed with a 3% hydrochloric acid solution in a mass ratio of 1:4, and steam was introduced into the mixture for 12 h. After the acid washing, the mixture was washed with deionized water until neutral, and then dried in an oven at 120° C. to obtain coconut shell columnar activated carbon E.
[0173] The characterization results show that the specific surface area of the coconut shell columnar activated carbon E obtained in this example is 1508.1 m 2 / g, pore volume 0.55cm 3 / g, the average pore size is 3.4nm; the strength is 98.9%, the phosphorus content is 217.9ppm, the sulfur content is 236.1ppm, and the chlorine content is 415.3ppm.
[0174] Examples 1-6
[0175] This embodiment provides a coconut shell columnar activated carbon, and the preparation steps are as follows:
[0176] (1) Pretreatment: The coconut shell was crushed and ground, passed through a 170-mesh sieve, and washed with deionized water for three times. After washing, it was dried in an oven at 120°C to obtain coconut shell powder.
[0177] (2) Carbonization: Weigh 200 g of the coconut shell powder obtained in step (1), add 800 mL of 1.0 mol / L sodium hydroxide solution, and soak at 85°C for 16 h. After the soaking, control the heating rate to 8°C / min, heat to 400°C for carbonization for 2 h, then cool to room temperature, wash with deionized water until neutral, and finally dry in an oven at 120°C to obtain a coconut shell carbonized material.
[0178] (3) Molding: The coconut shell carbonized material, casein glue and water are loaded into a kneader in a mass ratio of 100:20:30, kneaded evenly, extruded at 45°C, and dried at room temperature for 24 hours to obtain columnar charcoal.
[0179] (4) Impregnation: Sodium nitrate solid is dissolved in deionized water to prepare a sodium nitrate solution with a mass percentage concentration of 15%. The columnar carbon prepared in step (3) is mixed with the sodium nitrate solution in a mass ratio of 1:10, placed in a round-bottom flask, connected to a rotary evaporator, and rotary evaporated at room temperature and atmospheric pressure for one hour. After the impregnation is completed, the solid is filtered and dried in an oven at 120°C for 12 hours.
[0180] (5) Activation: The columnar carbon loaded with metal salt obtained in step (4) was heated to 1100°C for 12 h under nitrogen protection at a heating rate of 8°C / min, and water vapor was introduced at a flow rate of 1.0 mL / min for activation. After the calcination was completed, it was cooled to room temperature to obtain coconut shell columnar activated carbon.
[0181] (6) Acid washing: The coconut shell columnar activated carbon obtained in step (5) was mixed with a 3% hydrochloric acid solution in a mass ratio of 1:4, and steam was introduced into the mixture for 12 h. After the acid washing, the mixture was washed with deionized water until neutral, and then dried in an oven at 120° C. to obtain coconut shell columnar activated carbon F.
[0182] The characterization results show that the specific surface area of the coconut shell columnar activated carbon F obtained in this example is 1429.5 m 2 / g, pore volume 0.69cm 3 / g, the average pore size is 3.8nm; the strength is 98.6%, the phosphorus content is 204.4ppm, the sulfur content is 204.5ppm, and the chlorine content is 138.4ppm.
[0183] Examples 1-7
[0184] This embodiment provides a coconut shell columnar activated carbon, and the preparation steps are similar to those of Example 1, except that the binder used in step (3) is different. In this embodiment, the binder used in step (3) is coal tar. The other steps are the same as those of Example 1 and will not be repeated.
[0185] The characterization results show that the specific surface area of the coconut shell columnar activated carbon G obtained in this example is 1145.7 m 2 / g, pore volume 0.22cm 3 / g, the average pore size is 1.8nm; the strength is 97.2%, the phosphorus content is 874.2ppm, the sulfur content is 2523.9ppm, and the chlorine content is 534.7ppm.
[0186] Examples 1-8
[0187] This embodiment provides a coconut shell columnar activated carbon, and the preparation steps are similar to those of Example 1, except that the metal salt impregnation liquid used in step (4) is different. In this embodiment, the metal salt impregnation liquid used in step (4) is a sodium carbonate solution. The other steps are the same as those of Example 1 and will not be repeated.
[0188] The characterization results show that the specific surface area of the coconut shell columnar activated carbon H obtained in this example is 1326.4 m 2 / g, pore volume 0.81cm 3 / g, the average pore size is 4.7nm; the strength is 99.2%, the phosphorus content is 189.4ppm, the sulfur content is 192.6ppm, and the chlorine content is 148.6ppm.
[0189] Comparative Example 1-1
[0190] Comparative Example 1-1 provides a coconut shell columnar activated carbon, the preparation steps are similar to those of Example 1, except that the metal salt impregnation in step (4) is not performed. The other steps are the same as those of Example 1 and will not be described in detail.
[0191] The characterization results show that the specific surface area of coconut shell columnar activated carbon J obtained in comparative example 1-1 is 1268.7 m 2 / g, pore volume 0.76cm 3 / g, the average pore size is 4.2nm; the strength is 98.5%, the phosphorus content is 189.2ppm, the sulfur content is 242.6ppm, and the chlorine content is 181.5ppm.
[0192] Comparative Example 1-2
[0193] Comparative Example 1-2 provides a coconut shell columnar activated carbon, and the preparation steps are similar to those of Example 1, except that the metal salt impregnation solution used in step (4) is different. In Comparative Example 1-2, the metal salt impregnation solution is a lanthanum nitrate solution with a mass percentage concentration of 10%. The other steps are the same as those of Example 1 and are not repeated here.
[0194] The characterization results show that the specific surface area of coconut shell columnar activated carbon K obtained in Comparative Example 1-2 is 1283.7 m 2 / g, pore volume 0.81cm 3 / g, the average pore size is 4.8nm; the strength is 98.8%, the phosphorus content is 180.6ppm, the sulfur content is 192.6ppm, and the chlorine content is 201.8ppm.
[0195] Comparative Examples 1-3
[0196] Comparative Example 1-3 provides a coconut shell columnar activated carbon, the preparation steps are similar to those of Example 1, except that, in step (1), no sodium hydroxide solution impregnation is performed before carbonization. The other steps are the same as those of Example 1 and will not be described in detail.
[0197] The characterization results show that the specific surface area of the coconut shell columnar activated carbon I obtained in Comparative Examples 1-3 is 986.2 m 2 / g, pore volume 0.24cm 3 / g, the average pore size is 2.1nm; the strength is 95.4%, the phosphorus content is 6802.6ppm, the sulfur content is 4819.3ppm, and the chlorine content is 2513.8ppm.
[0198] The specific surface area, strength, pore volume and average pore diameter data of the activated carbon obtained in the above examples and comparative examples are shown in Table 1 below.
[0199] Table 1
[0200]
[0201] 1: The binder is coal tar;
[0202] II: No sodium hydroxide solution impregnation was performed before carbonization treatment.
[0203] Comparative Example 2-1
[0204] Comparative Example 2-1 provides a method for decomposing methyl chloroformate, comprising the following steps:
[0205] Commercial Egret activated carbon was placed in a tubular reactor, and a mixed gas was prepared by nitrogen and a 0.8 g / min solution of methyl chloroformate and dimethyl carbonate (methyl chloroformate and dimethyl carbonate were heated and gasified during the feeding process) and fed into the reactor (in the mixed liquid of methyl chloroformate and dimethyl carbonate, the concentration of methyl chloroformate was 1000 ppm by mass). The reaction temperature was set to 120 °C, the reaction pressure was 0.7 MPa, and the gas space velocity was 6000 h -1 The reactor outlet was connected to a jacketed product condenser with a condensation temperature of 5°C.
[0206] The decomposition rate of methyl chloroformate in Comparative Example 2-1 was 89.60%.
[0207] Comparative Example 2-2
[0208] Comparative Example 2-2 provides a method for decomposing methyl chloroformate, and the experiment is carried out in the same manner as Comparative Example 2-1, except that the activated carbon is replaced by the coconut shell columnar activated carbon J prepared in the above Comparative Example 1-1. The decomposition rate of methyl chloroformate in Comparative Example 2-2 is 95.48%.
[0209] Comparative Examples 2-3
[0210] Comparative Example 2-3 provides a method for decomposing methyl chloroformate, and the experiment is carried out in the same manner as Comparative Example 2-1, except that the activated carbon is replaced by the coconut shell columnar activated carbon K prepared in the above Comparative Example 1-2. The decomposition rate of methyl chloroformate in Comparative Example 2-3 is 94.38%.
[0211] Comparative Examples 2-4
[0212] Comparative Example 2-4 provides a method for decomposing methyl chloroformate, and the experiment is carried out in the same manner as Comparative Example 2-1, except that the activated carbon is replaced by the coconut shell columnar activated carbon I prepared in the above Comparative Example 1-3. The decomposition rate of methyl chloroformate in Comparative Example 2-4 is 85.27%.
[0213] Example 2-1
[0214] This example provides a method for decomposing methyl chloroformate, and the experiment is carried out in the same manner as in Comparative Example 2-1, except that the activated carbon is replaced with the coconut shell columnar activated carbon A prepared in Example 1-1. The decomposition rate of methyl chloroformate in this example is 99.91%.
[0215] Example 2-2
[0216] This example provides a method for decomposing methyl chloroformate, and the experiment is carried out in the same manner as in Comparative Example 2-1, except that the activated carbon is replaced with the coconut shell columnar activated carbon B prepared in Example 1-2. The decomposition rate of methyl chloroformate in this example is 99.96%.
[0217] Example 2-3
[0218] This example provides a method for decomposing methyl chloroformate, and the experiment is carried out in the same manner as in Comparative Example 2-1, except that the activated carbon is replaced with the coconut shell columnar activated carbon C prepared in Example 1-3. The decomposition rate of methyl chloroformate in this example is 99.78%.
[0219] Embodiment 2-4
[0220] This example provides a method for decomposing methyl chloroformate. The experiment was carried out in the same manner as in Comparative Example 2-1, except that the activated carbon was replaced with the coconut shell columnar activated carbon D prepared in Example 1-4, and the gas space velocity was adjusted to 10000 h -1 The decomposition rate of methyl chloroformate in this embodiment is 99.76%.
[0221] Embodiment 2-5
[0222] This example provides a method for decomposing methyl chloroformate. The experiment was carried out in the same manner as in Comparative Example 2-1, except that the activated carbon was replaced with the coconut shell columnar activated carbon E prepared in Example 1-5, and the gas space velocity was adjusted to 15000 h -1 The decomposition rate of methyl chloroformate in this embodiment is 99.88%.
[0223] Embodiment 2-6
[0224] This example provides a method for decomposing methyl chloroformate. The experiment was carried out in the same manner as in Comparative Example 2-1, except that the activated carbon was replaced with the coconut shell columnar activated carbon F prepared in Example 1-6, and the gas space velocity was adjusted to 25000 h -1 The decomposition rate of methyl chloroformate in this embodiment is 99.85%.
[0225] Embodiment 2-7
[0226] This example provides a method for decomposing methyl chloroformate. The experiment was carried out in the same manner as in Comparative Example 2-1, except that the activated carbon was replaced with the coconut shell columnar activated carbon B prepared in Example 1-2, and the gas space velocity was adjusted to 30000 h -1 The decomposition rate of methyl chloroformate in this embodiment is 99.87%.
[0227] Embodiment 2-8
[0228] This example provides a method for decomposing methyl chloroformate. The experiment was carried out in the same manner as in Comparative Example 2-1, except that the activated carbon was replaced with the coconut shell columnar activated carbon B prepared in Example 1-2, and the gas space velocity was adjusted to 15000 h -1 , the reaction temperature was adjusted to 130° C. The decomposition rate of methyl chloroformate in this example was 99.96%.
[0229] Embodiment 2-9
[0230] This example provides a method for decomposing methyl chloroformate. The experiment was carried out in the same manner as in Comparative Example 2-1, except that the activated carbon was replaced with the coconut shell columnar activated carbon B prepared in Example 1-2, and the gas space velocity was adjusted to 15000 h -1 , the reaction temperature was adjusted to 110° C. The decomposition rate of methyl chloroformate in this example was 99.94%.
[0231] Embodiment 2-10
[0232] This example provides a method for decomposing methyl chloroformate, and the experiment is carried out in the same manner as in Comparative Example 2-1, except that the activated carbon is replaced with the coconut shell columnar activated carbon G prepared in Example 1-7. The decomposition rate of methyl chloroformate in this example is 99.26%.
[0233] Example 2-11
[0234] This example provides a method for decomposing methyl chloroformate, and the experiment is carried out in the same manner as in Comparative Example 2-1, except that the activated carbon is replaced with the coconut shell columnar activated carbon H prepared in Example 1-8. The decomposition rate of methyl chloroformate in this example is 98.31%.
[0235] Some process parameters and experimental results of the above embodiments and comparative examples are shown in Table 2 below.
[0236] Table 2
[0237]
[0238] It can be seen from the above table that the coconut shell columnar activated carbon prepared in the embodiment of the present application is used for the decomposition of methyl chloroformate, which is beneficial to improve the decomposition rate.
[0239] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0240] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the contents of the attached claims, and the description and drawings can be used to explain the contents of the claims.
Claims
1. A method for preparing coconut shell columnar activated carbon, characterized in that: The steps include: The coconut shell powder is mixed with an alkaline solution and then carbonized to prepare a coconut shell carbonized material; The coconut shell carbonized material is mixed with a binder and a solvent and extruded to form a columnar carbon; The pillared carbon is mixed and impregnated with a metal salt solution to prepare a metal salt-loaded pillared carbon, wherein the metal salt solution includes one or more of a potassium salt solution and a sodium salt solution; The metal salt-loaded columnar carbon is calcined and activated to prepare coconut shell columnar activated carbon.
2. The method for preparing coconut shell columnar activated carbon according to claim 1, characterized in that: The metal salt solution includes one or more of sodium nitrate solution, potassium nitrate solution, sodium carbonate solution and potassium carbonate solution; Optionally, the metal salt solution includes one or both of a sodium nitrate solution and a potassium nitrate solution; Optionally, the mass percentage concentration of the metal salt solution is 5% to 15%.
3. The method for preparing coconut shell columnar activated carbon according to claim 1 or 2, characterized in that: The mass ratio of the pillared carbon to the metal salt solution is 1:(1-10); Optionally, the mass ratio of the columnar carbon to the metal salt solution is 1:(3-5).
4. The method for preparing coconut shell columnar activated carbon according to claim 1, characterized in that: The step of mixing coconut shell powder with alkaline solution and then carbonizing it satisfies one or more of the following conditions: (1) The carbonization temperature is 300°C to 480°C, and the time is 1h to 4h; (2) The heating rate of the carbonization process is 3°C / min~10°C / min; (3) The temperature of the mixed immersion of the coconut shell powder and the alkaline solution is 80° C. to 90° C., and the time is 16 h to 24 h; Optionally, the mass volume ratio of the coconut shell powder to the alkaline solution is (15g~25g): (100mL~300mL), wherein the concentration of the alkaline solution is 0.1mol / L~1.0mol / L; Optionally, the alkaline solution includes one or both of a sodium hydroxide solution and a potassium hydroxide solution; (4) The mesh size of the coconut shell powder is 100-250 meshes. Optionally, the mesh size of the coconut shell powder is 150-200 meshes.
5. The method for preparing coconut shell columnar activated carbon according to claim 1 or 4, characterized in that: The step of mixing the coconut shell carbonized material with a binder and a solvent and extruding the mixture to form a mold satisfies one or more of the following conditions: (1) The binder includes one or more of casein glue, coal tar, liquid asphalt, epoxy resin, urea-formaldehyde resin and modified starch. Optionally, the binder includes casein glue; (2) The mass ratio of the coconut shell carbonized material, the binder and the solvent is 100: (20-50): (5-30); (3) The solvent includes one or both of water and glycerol; (4) The extrusion molding temperature is 10°C to 45°C.
6. The method for preparing coconut shell columnar activated carbon according to claim 1 or 2, characterized in that: The steps of calcining and activating the metal salt-loaded columnar carbon meet one or more of the following conditions: (1) The calcination temperature is 900℃~1100℃ and the calcination time is 8h~12h; (2) The heating rate during the calcination process is 3℃ / min~10℃ / min; (3) Water vapor is introduced for activation at a flow rate of 0.5 mL / min to 1.5 mL / min.
7. The method for preparing coconut shell columnar activated carbon according to claim 1, characterized in that: Also includes: The step of acid washing the coconut shell columnar activated carbon; Optionally, in the pickling step, a hydrochloric acid solution with a mass percentage concentration of 3% to 5% is used, and the mass ratio of the hydrochloric acid solution to the coconut shell columnar activated carbon is (4 to 6):1; Optionally, the pickling time is 8h~12h.
8. A coconut shell columnar activated carbon, characterized in that: The specific surface area of the coconut shell columnar activated carbon is not less than 1100m 2 / g, the coconut shell columnar activated carbon is loaded with one or more of sodium oxide and potassium oxide; Optionally, the strength of the coconut shell columnar activated carbon is greater than 97%; Optionally, the pore volume of the coconut shell columnar activated carbon is 0.1 cm 3 / g~1cm 3 / g, average pore size is 1nm~10nm; Optionally, the coconut shell columnar activated carbon is prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the coconut shell columnar activated carbon as claimed in claim 8 in catalyzing the decomposition reaction of methyl chloroformate.
10. The use according to claim 9, characterized in that: Meet one or more of the following conditions: (1) The reaction temperature is 110℃~130℃, the reaction pressure is 0.5MPa~0.8MPa, and the gas space velocity is 6000h -1 ~30000h -1 ; (2) During the reaction, a protective gas is introduced at a flow rate of 500 mL / min to 1200 mL / min; (3) The methyl chloroformate is introduced in the form of a mixed liquid of methyl chloroformate and dimethyl carbonate, the mass flow rate of the mixed liquid is 0.8 g / min to 4.0 g / min, and the concentration of methyl chloroformate in the mixed liquid is 250 ppm to 10000 ppm by mass.